Assessment of the understanding of the patient and/or caregiver in relation to the drugs prescribed in an emergency care unit (Research, Society and Development, 2023)
This study aimed to assess the patients and/or caregivers level of understanding about the pharmacotherapeutic plan prescribed by the physician; identify and describe the frequency and types of errors in understanding the medical prescription by patients and caregivers, and know the profile of people who received a medical prescription for home use at the unit. Observational, cross-sectional, individual study, using a specific semi-structured questionnaire, approved by the research ethics committee, including patients and/or companions, aged 18 or over, treated at the Austin Emergency Care Unit in Nova Iguaçu, who received a medical prescription for home use, without cognitive or neurological impairment capable of hindering understanding. Of the 100 participants, 86% were patients and 14% were caregivers, 36% were self-declared brown, 36% were black and 28% were white. Only 13% had higher education. Only 18% of the participants answered all the questions related to the use of the medication correctly (route of administration, amount per dose, interval, frequency, duration of treatment, indication, conduct in case of discontinuation of treatment, and possibility of repeating the prescription). Questions related to dosage were considered essential to understanding, where only 59% answered the 3 items correctly and 11% did not answer any of them. The most frequent errors of understanding were conducted in case of forgetting (64%) and possible side effects (62%). The results point to the need for written and verbal communication strategies that allow a full understanding of the medical prescription, aiming at a better therapeutic result.